Huzurevinde yaşayan yaşlı bireylerin sağlıklı yaşam davranışlarının belirlenmesi / Healthy lifestyle behaviours of elderly people living in nursing homes - BALCI YAPALAK, AYŞE NUR (Bezmialem Vakıf University, 2020)
Introduction: Life expectancy at birth has been increasing in Turkey as it is in the world. However, a healthy life is as important as a long life and the most common health problem in old ages is non-communicable diseases. Prevention of non-communicable diseases is possible by developing healthy habits. The aim of the study is to determine the healthy lifestyle behaviors of the elderly people living in nursing homes. Methods: There are nine nursing homes in İstanbul administered by Ministry of Family, Labor and Social Services. This cross-sectional study was conducted in 5 of these nursing homes (Prof. Fahrettin Kerim- Nilüfer Gökay, Beylikdüzü, İzzet Baysal and Kartal Maltepe Nursing Home, Elderly Care and Rehabilitation Centers and Zeytinburnu Semiha Şakir Nursing Home), that approved the research to be conducted in their facilities. People who received special care services in institutions or who received normal care but had amnesia, loss of limbs, hearing or speech problems were not included in the study. 120 people were required to be included in the study according to the power analysis with 80% power and 5% margin of error. Each nursing home was considered as a cluster. The participants were chosen from the nursing home residents who were in the common area and agreed to participate in the study. A questionnaire that contains socio-demographic information, Health Promoting Lifestyle Profile II (HPLP-II) and the first part of Nottingham Health Profile Scale (NHP) were applied to the participants. 15/286 numbered ethic approval was obtained from Bezmialem Vakif University Non-Invasive Researches Ethics Committee on 30.07.2019. Findings: Average age of 120 participants was 75.8±7.8 and 40% of them (n=48) were women. 14.3% of participants (n = 17) never went to school and 42.9% (n = 51) got high school or higher education. 16.0% (n = 19) are married, 68.9% (n = 82) were widowed. 85.8% (n = 103) of them have at least one chronic disease, 29.5% (n = 33) of them smoke. The highest scores per question from the sub-dimensions of HPLP-II that participants received were spiritual growth and stress management, respectively and the lowest scores were health responsibility and physical activity, respectively. It was found that health responsibility is better in women than men (p <0.001), in widowed than divorced (p = 0.036), and in those with at least one chronic disease (p = 0.003). It was observed that as education increased, spiritual growth and total HPLP-II scores increased (r = 0.476 and 0.228, respectively). It was found that those with children (p = 0.045) were more physically active than those without children and those with chronic disease than without chronic disease (p = 0.006). The best sub-dimensions of NHP that participants got were pain, energy level and emotional reaction, respectively and the worst ones are sleep, social isolation and physical mobility, respectively. It was observed that men were physically more active than women (p = 0.037), and those who did not spend most of their life in Istanbul were more socially isolated than those who lived mostly in Istanbul (p = 0.047). It was found that as the age increased, the pain, physical activity and energy profiles of the people worsen (r = 0.307, 0.230, 0.217, respectively). It was observed that the pain and physical activity profiles of those with chronic diseases were worse than those without chronic diseases (p = 0.009, 0.002, respectively). It was found that as the stay time in the nursing home increased, the sleep of the individuals improved (r = -0.211). Conclusion: The scores obtained from scale sub-dimensions containing habits such as health responsibility, physical activity and sleep were worse than emotionally evaluating sub-dimensions. %30 of the participants continue smoking. More suitable and wide-ranged interventions are required for improvement of the lifestyle habits among elderly nursing home residents to promote better health.

{{abstract}}
Thesis (Medical)--Bezmialem Vakıf University, Faculty of Medicine, Department of Public Health, Istanbul, 2017
Keywords: Halk Sağlığı = Public Health; Halk Sağlığı Anabilim Dalı; Department of Public Health; Elderly health; Nursing home